Exploring factors driving social recruiting: The case of Australian organizations. Issue 3 (2nd July 2016) - Kashi, Kia; Zheng, Connie; Molineux, John
ABSTRACT: This study identifies key factors driving the organizational adoption of social recruiting technologies, such as LinkedIn, Facebook, and Twitter. The Technology, Organization, and Environment (TOE) framework, as an initial exploratory approach, is used to identify underlying factors of new technology adoption. Qualitative evidence collected from 12 Australian firms serves to specifically categorize key determinants of the organizational adoption of social recruiting technologies. It is found that apart from several TOE factors that significantly influence the organizational decision making with reference to social recruiting, top management support is seen as imperative for successful adoption of recruiting technologies. Formalization, comprehensiveness, and strategic orientation of organizational human resource departments are closely linked to adoption of social recruiting at the firm level. In addition, job applicants' readiness and local success stories have driven firms to adopt social recruiting technologies. The study extends and modifies the TOE model to provide the theoretical foundations of social recruiting in the context of Australian organizations and help human resource professionals and practitioners to gain a better understanding of key drivers of organizational social recruiting.